2020
DOI: 10.1101/2020.05.04.075713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelet miRNA bio-signature discriminates between dementia with Lewy bodies and Alzheimer disease

Abstract: _ 3 The paper explained Problem: Dementia with Lewy bodies (DLB) presents pathological and clinical overlap with both Alzheimer's (AD) and Parkinson's disease (PD), which impairs its correct diagnosis. Although numerous papers report peripheral biomarkers for AD, wellestablished biomarkers for DLB distinguishing it from AD are still missing. Platelet miRNA transcriptome was analyzed in several works, but their putative role as disease biomarkers for neurological disorders has not been assessed. It would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…Lastly, let‐7c was not described in PD previously, but other members of the let‐7 family showed deregulation in PD 32,43,47‐49 . In summary, most of the 12 biosignature miRNAs were earlier reported in α‐synucleinopathy 5‐7,10,21,22,33,36‐42 . This is relevant given that, if validated, our findings may have implications for other PD at‐risk cohorts, such as individuals with hyposmia or LRRK2 or GBA asymptomatic mutation carriers.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Lastly, let‐7c was not described in PD previously, but other members of the let‐7 family showed deregulation in PD 32,43,47‐49 . In summary, most of the 12 biosignature miRNAs were earlier reported in α‐synucleinopathy 5‐7,10,21,22,33,36‐42 . This is relevant given that, if validated, our findings may have implications for other PD at‐risk cohorts, such as individuals with hyposmia or LRRK2 or GBA asymptomatic mutation carriers.…”
Section: Discussionsupporting
confidence: 55%
“… 32 , 43 , 47 , 48 , 49 In summary, most of the 12 biosignature miRNAs were earlier reported in α‐synucleinopathy. 5 , 6 , 7 , 10 , 21 , 22 , 33 , 36 , 37 , 38 , 39 , 40 , 41 , 42 This is relevant given that, if validated, our findings may have implications for other PD at‐risk cohorts, such as individuals with hyposmia or LRRK2 or GBA asymptomatic mutation carriers.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Several studies have been so far reported studying miRNAs purified by different biological samples. Gamez-Valero et al [ 131 ], by profiling the whole miRNA transcriptome from platelet belonging to DLB, AD, and PD patients as well as to healthy controls (HC), identified a 7-miRNA biosignature with a high potential for the differential diagnosis between DLB and AD. In particular, they detected 3 groups of miRNAs, each specifically deregulated in one of the analyzed disorders.…”
Section: Mirna Expression Profilingmentioning
confidence: 99%